Food insecurity and barriers to supplemental food provision in the Mississippi Delta - Sophie Hathaway (Journal of Agriculture, Food Systems, and Community Development)
The Mississippi Delta has one of the highest concentrations of food-insecure households in the United States. Supplemental food provision has emerged as one avenue to addressing food insecurity in the Delta. Supplemental food providers (SFPs) in this study are defined as organizations focused on providing food (fresh produce, shelf-stable groceries, hot meals, etc.) at no cost to their clients. This qualitative study seeks to understand the current barriers to SFP efficacy in the Delta through conducting a thematic analysis of 29 qualitative interviews with SFP personnel. Results demonstrate that SFPs are valued community organizations that provide social services beyond feeding, but have operational, external, and relational barriers to maximum efficacy. Operational barriers refer to anything that impedes food distribution, like understaffing and lack of equipment, while external barriers are events that place SFPs under strain, like the COVID-19 pandemic. Relational barriers refer to the various functional relationships needed to distribute food in the MS Delta, whether it be between SFPs and clients or SFPs and donors. The implications of these barriers for SFP efficacy at both a local and national level are discussed. Additionally, this paper explores the potential role of SFPs in improving health outcomes in rural areas such as the Mississippi Delta through initiatives like client choice and community health hubs.